Water Conflict and Land Pickup at Baros-Cadasari with Mayora Company - Songga Aurora Abadi (Epistemik Press, 2020)
This journal discusses the role of law in ensuring that social changes occur in an orderly and orderly manner. social change for the sake of the sustainability of a society in a social environment. The investment permit to set up a company to exploit water in the Baros - Cadasari area is actually contrary to the 1945 Constitution Article 33 Paragraph (3) that the land, water, and natural resources of Indonesia are controlled by the State and are intended as much as possible for the prosperity of the people. This research was conducted using qualitative research, through a normative legal research approach, the data were analyzed prescriptively by taking an in-depth and detailed, and comprehensive approach to explore the research problem. The data used is secondary data, namely literature studies in the form of legislation, books, and scientific articles related to the writing of this journal. The results show that every society is always in a process of change that never ends, or in other words, social change is a symptom inherent in every society. The conflicts that occur over water and land are a series of conflicts with the community that has harmed the Indonesian people a lot, awareness of the conflicts that occur in turn that social change does not always occur gradually, through soft adjustments, but can also occur. in a revolutionary way.